Wychowanie do (nie)posłuszeństwa = Education for (dis)obedience - Czerepaniak-Walczak, Maria (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article addresses the issue of one of the aspects of civic education in educational interactions, namely obedience to the norms and rules of collective coexistence and disobedience to various forms of oppression that restrict the exercise of human and children?s rights. The author describes and analyses the specificity of obedience and disobedience, which may take on an infantile/childish form or a mature, courageous and responsible one.Each of these can be shaped and reinforced through experiences in the process of formal education. The paper is structured around the following hypothesis: both obedience and disobedience in educational interactions are related to students`, teachers` and parents` everyday life experiences, the type of social order and educational management policies and policies in education.
Keywords: edukacja formalna; Wychowanie obywatelskie; wychowanie do posłuszeństwa; nieposłuszeństwo obywatelskie; formal education; civic education; education for obedience; civil disobedience